Antagonistic activity of Lactobacillus acidophilus LA10 against Salmonella enterica serovar Enteritidis SE86 in mice - Scapin,Diane (2013)
Salmonella enterica serovar Enteritidis is one of the main pathogens responsible for foodborne illness in Brazil. Probiotic bacteria can play a role in defense and recovery from enteropathogenic -infections. In this study, the ability of Lactobacillus acidophilus LA10 to colonise and exert anta-gonistic effects in the gastrointestinal tract was tested before and during experimental infection in conventional mice contaminated with S. Enteritidis (SE86). A dose of 0.1 mL containing 10(8) viable cells of SE86 and L. acidophilus LA10 was orally administered by gavage to mice. The experiment was divided into groups. As a negative control, Group 1 was administered only sterile saline solution. As a positive control, Group 2 was administered only SE86. Group 3 was first administered SE86, and after 10 days, treated with L. acidophilus LA10. Group 4 was first administered L. acidophilus LA10,and after 10 days, challenged with SE86.The results demonstrated that a significant number of SE86 cells were able to colonize the gastrointestinal tract of mice, specifically in the colon and ileum. L. acidophilus LA10 demonstrated an antagonistic effect against SE86, with better results observed for Group 3 over Group 4. Thus, L. acidophilus LA10 shows potential antagonistic effects against S. Enteritidis SE86, especially if administered after infection.